Mountain bike terrain park injuries: an emerging cause of morbidity. Issue 4 (27th March 2011) - Ruest, N; Nguyen, M; Embree, T; Rowe, B H; Hagel, B E
Abstract : Background: The popularity of mountain biking (MB) has led to the development of commercial MB parks. Little is known about the injury profile and risk factors in these areas. Objective: To determine the injury profile and risk factors for severe injury among cyclists in MB parks. Design: Prospective case-control study. Cases were hospitalised cyclists injured in MB parks. Controls were cyclists injured in MB parks seen and discharged from the emergency department (ED). Setting: Four EDs in Calgary, Alberta, Canada. Participants: Recreational cyclists injured in a MB park who presented to one of the study EDs from May 2008 to August 2010. 351 patients were interviewed. Assessment of risk factors: Crash circumstances were captured through interviews and injury data through medical chart review. Main outcome measurements: Severe injury as defined by hospitalisation; levels within factors were compared using OR and 95% CI. Results: 23 participants were hospitalised (cases).The most common body region injured was the head/neck/face among cases, and the upper extremities among controls. 21% of cases and 9% of controls were female. A greater proportion of cases than controls were older than 25 years (22% vs 15%, respectively). Full-face helmets were used less among cases than controls (21% vs 41%, respectively). Arm and elbow protection was used more among cases than controls (arm: 13% vs 2%; elbow: 22% vs 8%). On univariate analyses, we found an indication of increased odds of severe injury among females (OR=2.8; 95% CI 0.96 to 8.06). Riding a new bicycle (OR=2.74; 95% CI 1.16 to 6.45) and cycling on grass compared with dirt (OR=7.06; 95% CI 1.21 to 41.33) increased the odds of severe injury. Conclusion: Preliminary analysis suggests surface and experience-related characteristics may increase the risk of severe injury. Case-control differences were noted in protective equipment use.